The power of the Nāth Yogīs: Yogic charisma, political influence and social authority - Bevilacqua, Daniela; Stuparich, Eloisa (Amsterdam University Press, 2022)
The volume collects a series of contributions that help reconstruct the recent history of the N.th tradition, highlighting important moments of self.reinterpretation in the "samprad.ya"s interaction with different social milieus. The leitmotif tying together the selection of articles is the authors explorations of the overlap between religious authority and political power. For example, in which ways do the N.ths hagiographical claim of possessing yogic charisma (often construed as supernatural powers, siddhis) translate into mundane expressions of socio.political power And how does it morph into the authority to reinterpret and recreate particular traditions The articles approach different aspects of the recent history of the N.th samprad.ya, spanning from stories of yog.s guiding kings in the petty principalities of the eighteenth century to gurus who sought prominence in the transnational environments of the twentieth century; examining some N.th lineages and institutions under the British Raj, in the history of Nepal, and in contemporary India
Keywords: Aufsatzsammlung; Macht; Autorität; Religion; Charisma; Kanpatha-Sekte